“The Eternal Triangle of Barrie Moviedom”: Reproducing Metropolitan Cinema Competition in the Hinterland - Armstrong, Aaron (Ontario History, 2021)
Between 1908 and 1938, Barrie went from having no permanent movie theatres to the city with the most per capita in the county. Barrie not only furnished a sizable audience, but one large enough to sustain multiple theatres that seated 600, reinforcing the importance of studying rural audiences. By examining the development of cinema, the struggles between theatre operators, and how local audiences interacted with the new medium it becomes clear that people in Barrie and comparable rural municipalities engaged with cinema in similar but not identical ways as those in large urban centres. This study shifts the current dialogue from one of metropole imposing change on the periphery to a better understanding of rural theatre culture as a unique entity worthy of study.